Cell Wall Invertase Is Essential for Ovule Development through Sugar Signaling Rather Than Provision of Carbon Nutrients - Liao, Shengjin (Plant Physiol, 2020)
Ovule formation is essential for realizing crop yield because it determines seed number. The underlying molecular mechanism, however, remains elusive. Here, we show that cell wall invertase (CWIN) functions as a positive regulator of ovule initiation in Arabidopsis (Arabidopsis thaliana). In situ hybridization revealed that CWIN2 and CWIN4 were expressed at the placenta region where ovule primordia initiated. Specific silencing of CWIN2 and CWIN4 using targeted artificial microRNA driven by an ovule-specific SEEDSTICK promoter (pSTK) resulted in a substantial reduction of CWIN transcript and activity, which blocked ovule initiation and aggravated ovule abortion. There was no induction of carbon (C) starvation genes in the transgenic lines, and supplementing newly forming floral buds with extra C failed to recover the ovule phenotype. This indicates that suppression of CWIN did not lead to C starvation. A group of hexose transporters was downregulated in the transgenic plants. Among them, two representative ones were spatially coexpressed with CWIN2 and CWIN4, suggesting a coupling between CWIN and hexose transporters for ovule initiation. RNA-sequencing analysis identified differentially expressed genes encoding putative extracellular receptor-like kinases, MADS-box transcription factors, including STK, and early auxin response genes in response to CWIN-silencing. Our data demonstrate the essential role of CWIN in ovule initiation, which is most likely to occur through sugar signaling instead of C nutrient contribution. We propose that CWIN-mediated sugar signaling may be perceived by, and transmitted through, hexose transporters or receptor-like kinases to regulate ovule formation by modulating downstream auxin signaling and MADS-box transcription factors.